Oncological transformation in vitro of hepatic progenitor cell lines isolated from adult mice - Rocío Olivera-Salazar; Mariano García-Arranz; Aránzazu Sánchez; Susana Olmedillas-López; Luz Vega-Clemente; Luis Javier Serrano; Blanca Herrera; Damián García-Olmo (Scientific Reports, 2022)
Abstract Colorectal cancer cells can transfer the oncogene KRAS to distant cells, predisposing them to malignant transformation (Genometastasis Theory). This process could contribute to liver metastasis; besides, hepatic progenitor cells (HPCs) have been found to be involved in liver malignant neoplasms. The objective of this study is to determine if mouse HPCs—Oval cells (OCs)—are susceptible to incorporate Kras GAT (G12D) mutation from mouse colorectal cancer cell line CT26.WT and if OCs with the incorporated mutation behave like malignant cells. To achieve this, three lines of OCs in different conditions were exposed to CT26.WT cells through transwell co-culture for a week. The presence of Kras G12D and capacity to form tumors were analyzed in treated samples by droplet digital PCR and colony-forming assays, respectively. The results showed that the Kras G12D mutation was detected in hepatic culture conditions of undifferentiated OCs and these cells were capable of forming tumors in vitro. Therefore, OCs are susceptible to malignant transformation by horizontal transfer of DNA with Kras G12D mutation in an undifferentiated condition associated with the liver microenvironment. This study contributes to a new step in the understanding of the colorectal metastatic process.